A case study on the impact of Ramadan on biomechanical and physiological markers in a female collegiate student-athlete - Amitrano, J.; Ameer, T.; Lewandowski, G.; Calabrese, L.; Seshadri, D. R. (Frontiers in Sports and Active Living, 2025)
This case study investigates the impact of Ramadan, a month of fasting and prayer, on a single female Division I collegiate athlete leveraging wearable technologies, Beyond Pulse and Whoop 4.0, and subjective questionnaires to collectively monitor biomechanical, physiological, and psychological changes before, during, and after Ramadan. Beyond Pulse monitors performance metrics, including distance, speed, and heart rate (HR), while the Whoop 4.0 focuses on physiological data such as HR, heart rate variability (HRV), sleep quality (including sleep duration and debt), and exertion metrics like strain and recovery. Subjective measures, including rating of perceived exertion (RPE), stress, and energy levels, were recorded daily to monitor load-response following training. Analyses revealed a 14.6% reduction in sleep performance during Ramadan and persisting post-Ramadan. Stress, muscle soreness, and energy all changed during Ramadan (p = 2.00 × 10-6; p = 0.001; p = 0.0058, respectively), with stress remaining elevated post-Ramadan (p = 0.028), likely driven by exams and disrupted circadian rhythm. Team-level analysis shows declines in distance during Ramadan (p = 9.00 × 10-4) and rebound afterward (p = 3.00 × 10-5), alongside shifts in workload (p = 0.024) and training impulse (TRIMP, p = 0.014), offering a baseline to distinguish from periodization of training and effects of Ramadan. These results illustrate how Ramadan combined with academic demands substantially effects both physiological and psychological well-being in a Division 1 female athlete. This case study, to our knowledge, is the first to use wearable technology and subjective measures to track Ramadan-related changes in a division 1 collegiate female athlete, offering insights into holistic monitoring.